Invasive fungal infection in patients with hematologic disorders in a Brazilian tertiary care hospital - Camplesi Junior,Milton (2017)
ABSTRACT INTRODUCTION: Invasive fungal infections (IFIs) are an important complication in immunocompromised individuals, particularly neutropenic patients with hematological malignancies. In this study, we aimed to verify the epidemiology and diagnosis of IFIs in patients with hematologic problems at a tertiary hospital in Goiânia-GO, Brazil. METHODS: Data from 117 patients, involving 19 cases of IFIs, were collected. The collected data included diagnosis methods, demographics, clinical characteristics, and in vitro susceptibility to different antifungal agents. Among the 19 cases, 12 were classified as proven IFI and 7 as probable invasive aspergillosis with detection of galactomannan in blood and presence of lung infiltrates in radiographic images. Logistic regression analysis showed that the proven and probable IFIs were associated with increased risk of death. Statistical analysis demonstrated that age, sex, and underlying disease were not independently associated with risk of death in IFI patients. RESULTS: Most bloodstream isolates of Candida spp. exhibited low minimum inhibitory concentrations (MICs) to all antifungal agents tested. Voriconazole and amphotericin had the lowest MICs for Aspergillus spp. and Fusarium spp., but Fusarium spp. showed the least susceptibility to all antifungals tested. Amphotericin B, fluconazole, and itraconazole were found to be inactive in vitro against Acremonium kiliense; but this fungus was sensitive to voriconazole. CONCLUSIONS: Considering the high number of IFI cases, with crude mortality rate of 6%, we could conclude that IFIs remain a common infection in patients with hematological malignancies and underdiagnosed ante mortem. Thus, IFIs should be monitored closely.